Surrealism in Latin American Literature - Nicholson, M. author. aut Link
XII, 267 p.
Keywords: Charting surrealism in Latin American literature from its initial appearance in Argentina in 1928 to the surrealist-inspired work of several writers in the 1970s, Melanie Nicholson argues that surrealism has exercised a significant and positive influence over twentieth-century Latin American literature, particularly poetry.